Worldwide productivity and research trend of publications concerning electroactive materials and spinal cord injury: A bibliometric study - Liu, Sirui; Song, Lin; Dai, Weishu; Liu, Mengdie; Zhang, Huijing; Zhang, Xueyan; Li, Hongyu; Liu, Xiu; Lv, Yan; Hu, Ying (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: We investigated the current state and trends in the area during the previous ten years using bibliometric approaches to evaluate the global scientific output of research on electroactive materials and spinal cord injury. Methods: Studies on spinal cord injury in electroactive materials that were published between 2012 and 2022 were located using the Web of science (WOS) . The software programs bibliometrix R-package and CiteSpace were used to do quantitative analyses of annual publications, nation, author, institution, journal source, co-cited references, and keywords. The studies were categorized by the research's main points using a qualitative analysis, and publications having more than 10 citations each year. Results：In the final analysis, 1,330 relevant papers or reviews were included. There is an increased tendency in both the average annual citation rate and the number of publications in the discipline. The United States and the University of Toronto are the countries and institutions that have contributed the most to this discipline, respectively. The majority of authors are from the China and United States. Zhang Y is the author with the most published articles and holds the top position in the cited author h-index species. The journal with the highest number of published articles is "disability and rehabilitation"; the journal is divided into 4 main areas including physics, materials, chemistry, molecular and biology. The keyword analysis revealed a shift in research hotspots from schwann cell, fracture, and urinary disorders to carbon-based materials, functional recovery, and surgery. Analysis of qualitative data revealed that the role and mechanism of injectable conductive hydrogels in spinal cord healing after damage is a hot topic of current study, with the mechanism primarily focusing on the inhibition of oxidative stress (Nrf2) and apoptosis (Casepase 3). Conclusion: Our bibliometric analysis indicates that research on electroactive materials for spinal cord injury remains an active field of study. Moreover, contemporary research is concentrated on carbon-based materials, functional rehabilitation, and surgery.